Implementation of Brotherhood and Literacy in Improving Human Resources in North Petukangan, South Jakarta - Rokimin; Hamdan Arief Hanif; Zhara Salsabila (Universitas Darunnajah, Jakarta, Indonesia, 2023)
Implementation of Ukhuwah and Literacy Concepts in Increasing Human Resources. Communities in Petukangan Utara, South Jakarta have low Ukhuwah and Literacy. This is caused by various factors, starting from the fact that the surrounding community, especially teenagers, participate in community activities and the few people who are aware of a good environment. Based on the problems above, Darunnjah Jakarta University students in their KKN launched a program in the form of Implementation of the Ukhuwah and Literacy Concepts in Human Resource Development. To achieve this, various activities were carried out, starting from visits to the village government to encouraging literacy policies at the village level. Conducting Socialization of the Ukhuwah and Literacy Concept Implementation program to Village Officials. Counseling the Implementation of Ukhuwah and Literacy Concepts to the Community, and Implementing Ukhuwah by participating in community activities.